Existence of multiple immunodeterminants in the type-specific capsular substance of group B type Ia streptococci. - Kane, J A (1978)
Rabbits immunized with group B, type Ia streptococci produce two distinct populations of protective antibodies. Evidence is presented indicating that these antibodies are directed against two major immunodeterminants which coexist in the specific type Ia antigen. Immunochemical data, using purified antibody preparations, indicate that the type substance, a sialic acid polymer consisting of galactose, glucose, glucosamine, and sialic acid, possesses two distinct immunodominant determinants, terminal sialic acid residues and a galactosyl oligosaccharide. Antibodies directed against either of these determinants were shown to possess in vivo and in vitro opsonic capabilities.